Managing creativity on the margins: a comparative study of Beijing’s Songzhuang Art District and Hangzhou’s White Horse Lake Creative Eco-City - Keane, Michael; Wen, W. (National Cheng Kung University - Institute of Creative Industries Design, 2013)
In the past decade the ‘creative cluster’ has become a driver of urban renewal in China. Many cluster developments attract human capital and investment to post-industrial spaces. This paper looks at two developments which are more post-agricultural than post-industrial: the first is Songzhuang, a large scale contemporary art community situated on the eastern fringe of Beijing, the second is Hangzhou’s White Horse Lake Creative Eco-City, a ‘mixed variety’ cluster model which integrates elements of art, fashion, design and animation. The common factor in both cases is how they came into existence. In both districts urban creative workers moved into a rural environment. Drawing on interviews with planners, officials, and residents we investigate the challenges of sustaining such fringe clusters.